Влияние интеллектуальной нагрузки работников it-сферы на их эмоциональное состояние - Соколова, B. C. (ХНУРЕ, 2019)
This article addresses the issue of the emotional state of a person involved in IT. Attention is paid to the phenomenon of emotional burnout due to chronic prolonged mental stressors.